Biomimetic Vasculatures by 3D‐Printed Porous Molds. Issue 39 (22nd July 2022) - Ching, Terry; Vasudevan, Jyothsna; Chang, Shu‐Yung; Tan, Hsih Yin; Sargur Ranganath, Anupama; Lim, Chwee Teck; Fernandez, Javier G.; Ng, Jun Jie; Toh, Yi‐Chin; Hashimoto, Michinao
Abstract: Despite recent advances in biofabrication, recapitulating complex architectures of cell‐laden vascular constructs remains challenging. To date, biofabricated vascular models have not yet realized four fundamental attributes of native vasculatures simultaneously: freestanding, branching, multilayered, and perfusable. In this work, a microfluidics‐enabled molding technique combined with coaxial bioprinting to fabricate anatomically relevant, cell‐laden vascular models consisting of hydrogels is developed. By using 3D porous molds of poly(ethylene glycol) diacrylate as casting templates that gradually release calcium ions as a crosslinking agent, freestanding, and perfusable vascular constructs of complex geometries are fabricated. The bioinks can be tailored to improve the compatibility with specific vascular cells and to tune the mechanical modulus mimicking native blood vessels. Crucially, the integration of relevant vascular cells (such as smooth muscle cells and endothelial cells) in a multilayer and biomimetic configuration is highlighted. It is also demonstrated that the fabricated freestanding vessels are amenable for testing percutaneous coronary interventions (i.e., drug‐eluting balloons and stents) under physiological mechanical states such as stretching and bending. Overall, a versatile fabrication technique with multifaceted possibilities of generating biomimetic vascular models that can benefit future research in mechanistic understanding of cardiovascular diseases and the development of therapeutic interventions is introduced. Abstract : A microfluidics‐enabled molding technique combined with coaxial bioprinting to fabricate anatomically‐relevant, cell‐laden vascular models consisting of hydrogels is demonstrated. The fabricated vascular model can be branched, 3D, and laden with relevant cells comprising vasculatures.